ANALYSIS OF LITERARY RELATIONSHIP IN THE LYRICAL CONTENT - Saidova Raykhonoy Abduganievna (International Engineering Journal For Research & Development, 2020)
This article studies structural semiotic approach to the literary text. It is about paradigmatic relations and structural semiotic analysis of poetic work in the sample of one course based on Rauf Parfi's poem about motherland.